Does Wealth Inequality Matter for Growth? The Effect of Billionaire Wealth, Income Distribution, and Poverty - Sutirtha Bagchi; Jan Svejnar (Institute for the Study of Labor (IZA), 2013)
A fundamental question in social sciences relates to the effect of wealth inequality on economic growth. Yet, in tackling the question, researchers have had to use income as a proxy for wealth. We derive a global measure of wealth inequality from Forbes magazine's listing of billionaires and compare its effect on growth to the effects of income inequality and poverty. We find that wealth inequality reduces economic growth, but when we control for the fact that some billionaires acquired wealth through political connections, the effect of politically connected wealth inequality is negative, while politically unconnected wealth inequality, income inequality, and initial poverty have no significant effect.
Keywords: D31; O40; O43; 330; economic growth; wealth inequality; income inequality; billionaires; political connections